2023
DOI: 10.1242/dev.201293
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling regulates salivary gland branching morphogenesis by modulating cell adhesion

Abstract: Loss of FGF signaling leads to defects in salivary gland branching, but the mechanisms underlying this phenotype remain largely unknown. We disrupted expression of Fgfr1 and Fgfr2 in salivary gland epithelial cells and find that both receptors function coordinately in regulating branching. Strikingly, branching morphogenesis in double knockouts is restored by Fgfr1/2 knock-in alleles incapable of engaging canonical RTK signaling, suggesting that additional FGF dependent mechanisms play a role during salivary g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 75 publications
0
12
1
Order By: Relevance
“…The first tyrosine kinase fusion to be identified was BCR-ABL. This fusion resulted from the translocation t (9,22), also known as the "Philadelphia chromosome". It involved the joining of the ABL1 tyrosine kinase genes on chromosome 9 with the BCR gene on chromosome 22, creating the BCR-ABL fusion oncoprotein.…”
Section: Chromosomal Rearrangementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first tyrosine kinase fusion to be identified was BCR-ABL. This fusion resulted from the translocation t (9,22), also known as the "Philadelphia chromosome". It involved the joining of the ABL1 tyrosine kinase genes on chromosome 9 with the BCR gene on chromosome 22, creating the BCR-ABL fusion oncoprotein.…”
Section: Chromosomal Rearrangementsmentioning
confidence: 99%
“…RTKs control important functions in tissue homeostasis, cell function, and mammalian development. These functions include tissue repair and regeneration, organ morphogenesis, cell proliferation and survival, and neovascularization 7–11 . Therefore, gaining a deeper understanding of RTKs can help identify potential targets for cancer detection and therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question of what functionality remains in the FCPG alleles and how these functions are engaged outside of canonical FGF signaling. Our previous results indicated that while FGFR1/2 regulate cell-matrix and cell-cell adhesion, these processes were not affected in Fgfr1 FCPG or Fgfr2 FCPG homozygous embryos (Ray et al, 2020;Ray and Soriano, 2023). Evidence suggests that both FGFR1 and FGFR2 can recruit SRC family kinases (SFKs).…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous Fgfr1 FCPG/FCPG embryos develop until at least E10.5, while Fgfr2 FCPG/FCPG mice are viable. The large disparity between the FCPG and null alleles for both receptors indicates that partial functionality remains in both the Fgfr1 FCPG and Fgfr2 FCPG alleles (Brewer et al, 2015; Ray et al, 2020; Ray and Soriano, 2023).…”
Section: Introductionmentioning
confidence: 99%